Recovery of soil carbon pools and C–N stoichiometry under drought in degraded tin-mined soils using organic, inorganic, and bio-amendments - RAHAYU RAHAYU; FARHAN ERDASWIN; RETNO ROSARIASTUTI; WIDYATMANI SIH DEWI; FATIMAH FATIMAH; AKTAVIA HERAWATI; NURUL ICHSAN (Asian Journal of Agriculture, 2025)
Abstract. Rahayu, Erdaswin F, Rosariastuti R, Dewi WS, Fatimah, Herawati A, Ichsan N. 2025. Recovery of soil carbon pools and C–N stoichiometry under drought in degraded tin-mined soils using organic, inorganic, and bio-amendments. Asian J Agric 9: 818-830. Large-scale tin mining on Bangka Island, Indonesia, has severely degraded soils, resulting in low carbon reserves and imbalanced C–N stoichiometry, particularly under seasonal drought. This study evaluated the effectiveness of an integrated amendment strategy to restore soil carbon pools and improve C–N stoichiometry under these challenging conditions. A 100-day screenhouse experiment was conducted on degraded tin-mined soil using a Completely Randomized Design. Treatments included municipal compost, dolomite, Lactic Acid Bacteria (LAB), and NPK fertilizer, applied individually and in combination. Key physicochemical properties, carbon pools, stoichiometric ratios, and their interrelationships were analyzed using ANOVA, Redundancy Analysis, and Pearson correlation. The integrated combination treatment was synergistically superior (ANOVA, p<0.01). The recovery of carbon pools was marked by a seven-fold surge in microbial biomass carbon to 703.73 mg kg-¹ and a near-doubling of the soil organic carbon stock to 29.21 Mg C ha-¹. The improvement in C–N stoichiometry was evidenced by the optimization of key microbial efficiency ratios, with the MBC/SOC ratio reaching 13.99% and the MBC/TN ratio increasing to 45.18%. Redundancy Analysis confirmed that compost-based treatments formed a distinct, functionally efficient group. Furthermore, Pearson correlation revealed the integrated nature of this recovery, showing a tight coupling between the accumulation of key carbon pools (SOC and MBC; r=0.909) and the enhancement of microbial C-use efficiency. In contrast, the dolomite amendment created a dysfunctional system by causing a massive accumulation of Dissolved Organic Carbon (DOC) to 279.18 mg kg-¹ without a corresponding increase in microbial biomass. A holistic, multi-ameliorant strategy anchored by a substantial organic matter base is essential for restoring ecosystem functions. This approach provides a robust and practical framework for the sustainable land management of degraded post-tin mining landscapes, offering a viable pathway to rebuild soil health and enhance drought resilience.